"One plate/three-reporter" assay format for the detection and validation of yeast two-hybrid interactions. (November 2004) - Evans, David R.H.; Swirsding, Kendra A.; Taillon, Bruce E.; Simons, Jan F.
We describe a novel assay format for the Gal4-based yeast two-hybrid-system, in which the readout from three different reporter genes is measured sequentially in a single microplate. Activation of the URA3, MEL1, and lacZ reporters in response to a protein-protein interaction is monitored by measuring sequentially: ( i ) growth in medium lacking uracil, ( ii ) α-galactosidase activity, and ( iii ) β-galactosidase. The data thus generated permit elimination of many false positive signals and provide a preliminary measurement of reporter activation-strength that may be confirmed by further analysis. The assay procedure is inexpensive and requires few liquid-handling steps. It is appropriate for automated high-throughput interaction mating assays, validation of putative interactor strains and hybrid-protein self-activator tests.